Optimization of Cultivation Settings of Chlorella Grown in Indoor Photobioreactor and Assessment as Superfood - Talitha Maritza Putri Tara; Hadi Suhardjono; Saefur Rohman (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
Microalgae are microorganisms with great potential as a superfood. Microalgae can serve as an alternative food source. One of their ecosystems is freshwater, where they can be cultivated on a small scale using indoor farming systems, especially in urban areas. This is because microalgae can live anywhere as long as their growth factors are fulfilled. This becomes a bright spot for agriculture in Indonesia, where land is becoming increasingly limited, causing millennial farmers to struggle with conventional cultivation. Therefore, indoor farming systems with IoT can become an alternative solution that supports food security and more effective microalgae cultivation. Microalgae are photosynthetic unicellular organisms influenced by several factors, including pH and light intensity. pH plays an important role in enzyme activity and nutrient availability, while light intensity affects biomass, cell density, and nutritional content. Both factors are crucial in determining biomass, cell density and protein content. However, studies on the combined effect of pH and light intensity on protein content in microalgae are still limited. Thus, this research aims to investigate the influence of pH and light intensity on protein content in an indoor farming system with IoT. The findings are expected to contribute valuable knowledge about optimal pH and light conditions for maximizing protein content in microalgae cultivation as a superfood. Then, according to the result, the combined interaction is 7 pH and 3000 lux light intensity is the optimal for cultivation of microalgae, which is much higher than other combines.